EFL Students’ Engagement during Emergency Remote Teaching: Does Technology Matter? - Hanifah, Rahma Ainun; Setyaningsih, Endang; Sumardi, Sumardi (Journal of Languages and Language Teaching, 2022)
Amidst Covid-19, teachers, and students in many regions are forced to shift to Emergency Remote Teaching (ERT). This ERT context has attracted researchers to re-investigate dimensions of teaching and learning within this new situation. This paper reports an investigation on the students’ engagement during  ERT in a tertiary EFL setting. Two aspects are highlighted: description of the students’ engagement and its interplay with the choice of teaching-learning platforms.  Questionnaires, interviews, and artifacts were used to collect data. A combination of descriptive statistics and a thematic model of analysis were used to analyze the data. The total respondents of this study were five EFL students in the 6th-grade semester at a university in Surakarta. The researcher employed a case study methodology and use two data, primary data, and secondary data. For the primary data, the researcher used the result of interviews and questionnaires. The secondary data is additional data to get the data. The secondary data which is used is an artifact. The study revealed that all three kinds of engagement: cognitive, behavioral, and emotional, were observed in both high and low bandwidth platforms. This implies that there is another factor other than technology that plays a significant role in engaging the students to learn. Considering the cost and the infrastructure readiness, it is suggested that teachers focus on implementing the principles of good teaching instead of glorifying the use of sophisticated technology. In terms of technology use, it is recommended to choose the one that provides better accessibility and wider access for the students.